ECONOMIC POLICY OF DEVELOPED MARKET ECONOMIES TOWARDS PUBLIC COMPANIES - Petrović, Jelena (Economics of Agriculture, 2011)
Public companies perform their economic duty of public interest which has been defined by the Law on Public Companies and other, similar laws or regulations, whereas state companies are in the possession of the state and they perform any kind of duty. The most important characteristic of public companies is the production and distribution of essential goods of great importance for the economy and society. In this paper, the author pays special attention to the process of public company privatization in the developed countries of the world, namely in Great Britain, France and the United States of America.